QUADRUPLE FIXED POINT THEOREMS FOR (Î±,Ïˆ) - CONTRACTIVE TYPE MAPPINGS IN PARTIALLY ORDERED METRIC SPACES - ughade, manoj; Sanodia, P. L.; Gupta, Arvind; Pandey, Amit Kumar (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
In this paper, we determine some quadruple fixed point theorems for nonlinear contractive mappings in the framework of a metric space enclosed with partial order. We prove the uniqueness of a quadruple fixed point for such mappings in this setup. Also, we introduce some examples to illustrate the effectiveness of our results.